Using CBM to Identify Advanced Learners in the General Education Classroom. (January 2014) - Sulak, Tracey N.
Identification of gifted and talented students presents a conceptual and practical challenge for educators. On the one hand, giftedness can be represented by potential, a difficult trait to measure reliably given the multifaceted approach supported by many gifted programs. On the other hand, some behaviors that are indicative of potential, especially in academic areas, may only develop if students are provided with adequate experiences and advanced instruction. Vygotsky suggested instruction leads development, which supports the idea of offering advanced instruction to encourage the development of gifts and talents. This developmental approach to giftedness supports instructional practices based on student needs as opposed to labels, which is in direct opposition to the absolutist approach to giftedness. Under an absolutist paradigm, traditionally underserved populations are often excluded from gifted programming because intelligence tests or other normative procedures fail to identify undeveloped talents and gifts. To provide adequate programming for diverse populations, the identification procedures must be connected to the instructional programming, and for teachers, this shift means maximizing the development of all students by differentiating instruction based on needs rather than classifications or labels. This article describes the use of curriculum-based measurements in identifying gifted students.